1988
DOI: 10.1103/physreva.37.880
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on the Davydov soliton

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…This again shows clearly that the new wavefunction in the improved model contains exactly two quanta, instead of three quanta [21,22], when compared with the Davydov wave function containing one quantum), with the nonlinear coupling energy, G p , and a binding energy, E BP , determination of the features of the new soliton are greatly increased and larger by about three and twenty times than Davydov's soliton due to simultaneous changes in the Hamiltonian and wave function. In other word, a new interaction between the acoustic vibration of the amino acid and amide-I is added in the Hamiltonian, wave function with the quasi-coherent twoquantum state are used for the system in the improved model, thus the new soliton becomes very stability.…”
Section: Fig 16mentioning
confidence: 77%
“…This again shows clearly that the new wavefunction in the improved model contains exactly two quanta, instead of three quanta [21,22], when compared with the Davydov wave function containing one quantum), with the nonlinear coupling energy, G p , and a binding energy, E BP , determination of the features of the new soliton are greatly increased and larger by about three and twenty times than Davydov's soliton due to simultaneous changes in the Hamiltonian and wave function. In other word, a new interaction between the acoustic vibration of the amino acid and amide-I is added in the Hamiltonian, wave function with the quasi-coherent twoquantum state are used for the system in the improved model, thus the new soliton becomes very stability.…”
Section: Fig 16mentioning
confidence: 77%
“…Some numerical simulations indicated that the Davydov soliton is not stable at the biological temperature of 300 K [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Other simulations indicated that the Davydov soliton was stable at 300 K [30][31][32][33][34][35][36][37][38][39], but they were based on the classical equations of motion which were likely to yield unreliable estimates of the stability of the soliton [13][14][15][16][17][18]. The simulations based on the 2 | D 〉 state in Eq.…”
Section: Review Articlementioning
confidence: 99%
“…Since the dynamical equations used in the simulations are not equivalent to the dinger o Schr equation, the stability of the soliton obtained by these numerical simulations is unavailable or unreliable. The simulation [34] based on the 1 | D 〉 state in Eq. (3) with the thermal treatment of Davydov [31][32][33], where the equations of motion are derived from a thermally averaged Hamiltonian, yields the confusing result that the stability of the soliton is enhanced with the increase in temperature, predicting that the 1 | D 〉 -type soliton is stable in the region of biological temperature.…”
Section: Review Articlementioning
confidence: 99%
“…Subsequently, Cruzeiro et al 105 used also the thermodynamic average Hamiltonian H T = ν ρ νν H νν mentioned above, but H νν = D 1 |(H ex + H int + H ph )|D 1 . From again i ∂ϕn ∂t = ∂HT ∂ϕ * n and i ∂βn,q ∂t = ∂HT ∂β * n,q they obtained the dynamic equations of ϕ n and β n,q , respectively, where β * n,q + β −q,n = − ν|U + n (a + q + a −q )U n |ν , which are all nonlinear Schrödinger equations.…”
Section: Investigations On Thermal Stability Of the Davydov Solitons mentioning
confidence: 99%
“…This is due to the fact that previous analytical and numerical studies [12][13][14][15][16][17][18][19][20][21][22][23][84][85][86][87][88][89][90][91]104,105 have not adequately addressed the effects of thermal phonons, which may act to disperse exciton energy. Thus they finished a numerical calculation, in which they indicated that the excitations are strongly dispersed at physiological temperature.…”
Section: Investigations On Thermal Stability Of the Davydov Solitons mentioning
confidence: 99%